2017
DOI: 10.1007/s10544-017-0191-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of microRNAs directly from body fluids using a base-stacking isothermal amplification method in a point-of-care device

Abstract: MicroRNAs have been proposed to be a class of biomarkers of disease as expression levels are significantly altered in various tissues and body fluids when compared to healthy controls. As such, the detection and quantification of microRNAs is imperative. While many methods have been established for quantification of microRNAs, they typically rely on time consuming handling such as RNA extraction, purification, or ligation. Here we describe a novel method for quantification of microRNAs using direct amplificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…However, we have previously shown that ncR-NAs measured with a multiplex assay (≤4 h) yield comparable results. 39 Emerging technology may soon provide the ability to measure ncRNAs field-side using a portable device within 1 h. [52][53][54] Until that time, balance and neurocognitive testing remain more expedient adjuncts. However, these assessments usually require an experienced healthcare provider, and many youth or high school competitions/practices do not have an experienced provider present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have previously shown that ncR-NAs measured with a multiplex assay (≤4 h) yield comparable results. 39 Emerging technology may soon provide the ability to measure ncRNAs field-side using a portable device within 1 h. [52][53][54] Until that time, balance and neurocognitive testing remain more expedient adjuncts. However, these assessments usually require an experienced healthcare provider, and many youth or high school competitions/practices do not have an experienced provider present.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have previously shown that ncRNAs measured with a multiplex assay (≤4 h) yield comparable results 39 . Emerging technology may soon provide the ability to measure ncRNAs field‐side using a portable device within 1 h 52–54 . Until that time, balance and neurocognitive testing remain more expedient adjuncts.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is based on the use of probe-functionalized platinum nanoparticles that electrochemically detect the miRNA target strand, without the requirement of prior amplification. Another system based on microfluidic cards and isothermal base-stacking amplification allowed for direct one-step miRNA detection from body fluids in <60 min [157]. The results of a fluorescent-based microfluidic device that was tested to diagnose early breast-cancer stages by screening miRNA-21 quantities concurred with RT-qPCR, while working faster and more straightforward [158].…”
Section: Future Outlookmentioning
confidence: 99%
“…The system allows the multiplexed profiling of miRNA at sub-femtomolar concentration. Interestingly, Williams et al [58] proposed a miRNA detection technique able to amplify miRNAs directly in body fluids, avoiding upstream sample preparation. The technique, based on isothermal target amplification, has a sensitivity positioned in the femtomolar range.…”
Section: Technologies For Microrna Analysismentioning
confidence: 99%
“…The presence of microRNA promotes base-stacking hybridization, and subsequent amplification between two universal strands, under isothermal conditions. A sensitivity in the range of femtomolar is provided [58] Northern blotting Tissues An highly efficient microRNAs detection method based on northern blot analysis was set-up using LNA (locked nucleic acid) probes able to increase the sensitivity of at least 10-fold compared to conventional DNA probes [59] Bead-based flow Cytometry…”
Section: Plasmamentioning
confidence: 99%